2021
DOI: 10.1111/ele.13707
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution promotes fluctuation‐dependent species coexistence

Abstract: Recent studies have demonstrated that rapid contemporary evolution can play a significant role in regulating population dynamics on ecological timescales. Here we identify a previously unrecognised mode by which rapid evolution can promote species coexistence via temporal fluctuations and a trade‐off between competitive ability and the speed of adaptive evolution. We show that this interaction between rapid evolution and temporal fluctuations not only increases the range of coexistence conditions under a glean… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 58 publications
2
34
1
Order By: Relevance
“…These include, for example, the evolution of a defence trait in a prey species that equalises the competitive ability of its consumers, and thereby promotes their coexistence (van Velzen, 2020 ). Rapid evolution can also promote fluctuation‐dependent coexistence by changing the functional response of consumers to resources (Yamamichi & Letten, 2021 ) or promote exclusion when local adaptation prevents the colonisation of later‐arriving competitors (Leibold et al, 2019 ; Loeuille & Leibold, 2008 ; Thompson & Fronhofer, 2019 ; Urban & De Meester, 2009 ). The breadth of results showing how evolution shapes competitive outcomes necessitates an integrated theoretical framework for understanding the eco‐evolutionary dynamics of species coexistence.…”
Section: Introductionmentioning
confidence: 99%
“…These include, for example, the evolution of a defence trait in a prey species that equalises the competitive ability of its consumers, and thereby promotes their coexistence (van Velzen, 2020 ). Rapid evolution can also promote fluctuation‐dependent coexistence by changing the functional response of consumers to resources (Yamamichi & Letten, 2021 ) or promote exclusion when local adaptation prevents the colonisation of later‐arriving competitors (Leibold et al, 2019 ; Loeuille & Leibold, 2008 ; Thompson & Fronhofer, 2019 ; Urban & De Meester, 2009 ). The breadth of results showing how evolution shapes competitive outcomes necessitates an integrated theoretical framework for understanding the eco‐evolutionary dynamics of species coexistence.…”
Section: Introductionmentioning
confidence: 99%
“… The gleaner–opportunist trade‐off and fluctuation‐mediated stable coexistence via relative nonlinearity. (a) Fluctuation‐mediated stable coexistence is possible via negative frequency‐dependence (NFD) when the orange species stabilizes population cycles and prefers fluctuating environments whereas the blue species promotes population cycles and prefers stable environments (Yamamichi & Letten, 2021 ). (b) A conceptual figure showing requirements (zero net growth isocline, ZNGI; solid and dashed lines) and impacts (dotted arrows) of two species on the mean and variance of a single resource (Chase & Leibold, 2003 ; Yamamichi & Letten, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many potential resolutions to April 19, 2021 15/19 this paradox have been proposed such as chaotic dynamics [25], temporal heterogeneity [26], spatial heterogeneity [27], limitation by factors other than resource availability (e.g. predation) [28], or rapid evolution [29]. Recent work has suggested that both thermodynamic inhibition [6] and metabolic trade-offs [7] can allow more survivors than substrates, though it has since been suggested that metabolic trade-offs only support increased diversity for a very narrow and specific parameter range [30].…”
Section: Discussionmentioning
confidence: 99%